Situation of Obstetric Fistula in a Marginalized Teagarden Community of Bangladesh: A Qualitative Study - Biswas, Animesh; Doraiswamy, Sathyanarayanan; Halim, Abdul; Md. Abdullah, Abu Sayeed (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: This study aims to explore why and how difficult it is for obstetric fistula patients living in the underprivileged teagardens community of Bangladesh. Methods: It was a qualitative study conducted in 10 teagardens with approximately fifty thousand population. Five case studies followed by five Focus Group Discussions (FDG) were conducted in places where obstetric fistulas were identified. Results: The mean age of the women was 41 years and the mean duration of suffering was 19 years. All of them got married before the age of 15 and became pregnant in the following year. One woman was divorced, two were separated and two were living with their husband. Only one of them received treatment from a tertiary center but did not continue due to economic constraints; rest of them were never exposed to any treatment or care. They believed that it would be recovered over time. All of them were neglected in their society and were deprived from all social and religious activities in the community. FGDs findings represent that poverty, lack of knowledge and perception are the significant barriers. Conclusions: Underprivileged communities in the teagardens in Bangladesh are far behind in terms of access to quality health care services. Obstetric fistula is particularly still being under reported and undermined and focused intervention is required to eliminate fistula among them.